Pemberdayaan Pasien Kanker Melalui Spiritual Care Berbasis Psikoedukasi untuk Meningkatkan Kesejahteraan Psikologis - Fathiya Luthfil Yumni; Firman Firman; Ummi Masrufah Maulidiyah; Ina Fasira; Ira Purnamasari; Febriyanto Firman Wijaya (Journal of Community Development, 2026)
Cancer not only affects physical health but also causes psychological and spiritual problems for patients. Individuals diagnosed with cancer often experience anxiety, depression, and hopelessness, which can significantly reduce their quality of life. This community service activity aimed to provide psychosocial support through the implementation of psychoeducation-based spiritual care using innovative media, namely Virtual Reality (VR), at the Indonesian Cancer Foundation in Surabaya. The methods included socialization, preparation, intervention implementation (pre-test, material presentation, guided imagery practice through VR, and post-test), and evaluation. The participants consisted of 28 cancer patients, with the majority aged 36–45 years (53.6%). The findings showed that the patients’ psychological well-being increased from 64.3% (low category) before the intervention to 85.7% (high category) after the intervention. Conclusion: These findings indicate that the application of psychoeducation-based spiritual care through VR is effective in helping cancer patients enhance their calmness, motivation, and overall quality of life.